Digital Financial Application Literacy for MSMEs - Putri, Intan Lifinda Ayuning (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute substantially to Indonesia’s economic growth, yet many continue to struggle with limited financial literacy and low digital readiness, particularly in managing routine bookkeeping. This community service program aims to strengthen MSME financial management skills by integrating financial literacy education with practical training using the BukuWarung digital application. Employing a service-learning approach, the program was conducted through preparation, training, simulation, and evaluation stages involving 15 MSME actors across various sectors. The results indicate significant improvement, with participants’ average understanding scores increasing from 42% before training to 81% after training, accompanied by greater accuracy and independence in recording transactions digitally. These findings demonstrate that combining conceptual learning with hands-on digital practice effectively enhances MSME financial capability. The program concludes that sustained mentoring and extended intervention duration are necessary to ensure long-term adoption of digital bookkeeping practices and support MSME business sustainability.